Chronic inflammation decreases arcuate kisspeptin expression in male sheep - AN Renwick; BK Whitlock; CC Nestor; JA Daniel; L Strickland; AS Lear; M Adkins; C Griffin; A Esteller-Vico (Domestic Animal Endocrinology, 2024)

How useful is genomic data for predicting maladaptation to future climate? - Brandon M. Lind; Rafael Candido‐Ribeiro; Pooja Singh; Mengmeng Lu; Dragana Obreht Vidakovic; Tom R. Booker; Michael C. Whitlock; Sam Yeaman; Nathalie Isabel; Sally N. Aitken (Global Change Biology, 2024)
Methods using genomic information to forecast potential population maladaptation to climate change or new environments are becoming increasingly common, yet the lack of model validation poses serious hurdles toward their incorporation into management and policy. Here, we compare the validation of maladaptation estimates derived from two methods—Gradient Forests (GF offset ) and the risk of non‐adaptedness (RONA)—using exome capture pool‐seq data from 35 to 39 populations across three conifer taxa: two Douglas‐fir varieties and jack pine. We evaluate sensitivity of these algorithms to the source of input loci (markers selected from genotype–environment associations [GEA] or those selected at random). We validate these methods against 2‐ and 52‐year growth and mortality measured in independent transplant experiments. Overall, we find that both methods often better predict transplant performance than climatic or geographic distances. We also find that GF offset and RONA models are surprisingly not improved using GEA candidates. Even with promising validation results, variation in model projections to future climates makes it difficult to identify the most maladapted populations using either method. Our work advances understanding of the sensitivity and applicability of these approaches, and we discuss recommendations for their future use.

The immediate costs and long‐term benefits of assisted gene flow in large populations - Jared A. Grummer; Tom R. Booker; Remi Matthey‐Doret; Pirmin Nietlisbach; Andréa T. Thomaz; Michael C. Whitlock (Conservation Biology, 2022)
With the genetic health of many plant and animal populations deteriorating due to climate change outpacing adaptation, interventions, such as assisted gene flow (AGF), may provide genetic variation necessary for populations to adapt to climate change. We ran genetic simulations to mimic different AGF scenarios in large populations and measured their outcomes on population‐level fitness to determine circumstances in which it is worthwhile to perform AGF. In the absence of inbreeding depression, AGF was beneficial within a few generations only when introduced genotypes had much higher fitness than local individuals and traits affecting fitness were controlled by a few genes of large effect. AGF was harmful over short periods (e.g., first ∼10–20 generations) if there was strong outbreeding depression or introduced deleterious genetic variation. When the adaptive trait was controlled by many loci of small effect, the benefits of AGF took over 10 generations to realize—potentially too long for most climate‐related management scenarios. The genomic integrity of the recipient population typically remained intact following AGF; the amount of genetic material from the donor population usually constituted no more of the recipient population's genome than the fraction of the population introduced. Significant genomic turnover (e.g., >50% replacement) only occurred when the selective advantage of the adaptive trait and translocation fraction were extremely high. Our results will be useful when adaptive management is used to maintain the genetic health and productivity of large populations under climate change.

Variation in recombination rate affects detection of outliers in genome scans under neutrality - Tom R. Booker; Sam Yeaman; Michael C. Whitlock (Molecular Ecology, 2020)
Genome scans can potentially identify genetic loci involved in evolutionary processes such as local adaptation and gene flow. Here, we show that recombination rate variation across a neutrally evolving genome gives rise to mixed sampling distributions of mean F ST ( ), a common population genetic summary statistic. In particular, we show that in regions of low recombination the distribution of estimates has more variance and a longer tail than in more highly recombining regions. Determining outliers from the genome‐wide distribution without taking local recombination rate into consideration may therefore increase the frequency of false positives in low recombination regions and be overly conservative in more highly recombining ones. We perform genome scans on simulated and empirical Drosophila melanogaster data sets and, in both cases, find patterns consistent with this neutral model. Similar patterns are observed for other summary statistics used to capture variation in the coalescent process. Linked selection, particularly background selection, is often invoked to explain heterogeneity in across the genome, but here we point out that even under neutrality, statistical artefacts can arise due to variation in recombination rate. Our results highlight a flaw in the design of genome‐scan studies and suggest that without estimates of local recombination rate, interpreting the genomic landscape of any summary statistic that captures variation in the coalescent process will be very difficult.

Genomic islands of divergence infer a phenotypic landscape in Pacific lamprey - Jon E. Hess; Jeramiah J. Smith; Nataliya Timoshevskaya; Cyndi Baker; Christopher C. Caudill; David Graves; Matthew L. Keefer; Andrew P. Kinziger; Mary L. Moser; Laurie L. Porter; Greg Silver; Steven L. Whitlock; et al. (Molecular Ecology, 2020)
High rates of dispersal can breakdown coadapted gene complexes. However, concentrated genomic architecture (i.e., genomic islands of divergence) can suppress recombination to allow evolution of local adaptations despite high gene flow. Pacific lamprey ( Entosphenus tridentatus ) is a highly dispersive anadromous fish. Observed trait diversity and evidence for genetic basis of traits suggests it may be locally adapted. We addressed whether concentrated genomic architecture could influence local adaptation for Pacific lamprey. Using two new whole genome assemblies and genotypes from 7,716 single nucleotide polymorphism (SNP) loci in 518 individuals from across the species range, we identified four genomic islands of divergence (on chromosomes 01, 02, 04, and 22). We determined robust phenotype‐by‐genotype relationships by testing multiple traits across geographic sites. These trait associations probably explain genomic divergence across the species’ range. We genotyped a subset of 302 broadly distributed SNPs in 2,145 individuals for association testing for adult body size, sexual maturity, migration distance and timing, adult swimming ability, and larval growth. Body size traits were strongly associated with SNPs on chromosomes 02 and 04. Moderate associations also implicated SNPs on chromosome 01 as being associated with variation in female maturity. Finally, we used candidate SNPs to extrapolate a heterogeneous spatiotemporal distribution of these predicted phenotypes based on independent data sets of larval and adult collections. These maturity and body size results guide future elucidation of factors driving regional optimization of these traits for fitness. Pacific lamprey is culturally important and imperiled. This research addresses biological uncertainties that challenge restoration efforts.

Background selection and F ST : Consequences for detecting local adaptation - Remi Matthey‐Doret; Michael C. Whitlock (Molecular Ecology, 2019)
Background selection is a process whereby recurrent deleterious mutations cause a decrease in the effective population size and genetic diversity at linked loci. Several authors have suggested that variation in the intensity of background selection could cause variation in F ST across the genome, which could confound signals of local adaptation in genome scans. We performed realistic simulations of DNA sequences, using recombination maps from humans and sticklebacks, to investigate how variation in the intensity of background selection affects F ST and other statistics of population differentiation in sexual, outcrossing species. We show that, in populations connected by gene flow, Weir and Cockerham's (1984; Evolution , 38 , 1358) estimator of F ST is largely insensitive to locus‐to‐locus variation in the intensity of background selection. Unlike F ST , however, d XY is negatively correlated with background selection. Moreover, background selection does not greatly affect the false‐positive rate in F ST outlier studies in populations connected by gene flow. Overall, our study indicates that background selection will not greatly interfere with finding the variants responsible for local adaptation.

Trends in catchment processes and lake evolution during the late-glacial and early- to mid-Holocene inferred from high-resolution XRF data in the Yellowstone region - Yanbin Lu; Sherilyn C. Fritz; Jeffery R. Stone; Teresa R. Krause; Cathy Whitlock; Erik T. Brown; James V. Benes (Journal of Paleolimnology, 2017)

Growth and annual survival estimates to examine the ecology of larval lamprey and the implications of ageing error in fitting models - L. D. Schultz; B. E. Chasco; S. L. Whitlock; M. H. Meeuwig; C. B. Schreck (Journal of Fish Biology, 2017)
This study used existing western brook lamprey Lampetra richardsoni age information to fit three different growth models ( i.e. von Bertalanffy, Gompertz and logistic) with and without error in age estimates. Among these growth models, there was greater support for the logistic and Gompertz models than the von Bertalanffy model, regardless of ageing error assumptions. The von Bertalanffy model, however, appeared to fit the data well enough to permit survival estimates; using length‐based estimators, annual survival varied between 0·64 (95% credibility interval: 0·44–0·79) and 0·81 (0·79–0·83) depending on ageing and growth process error structure. These estimates are applicable to conservation and management of L. richardsoni and other western lampreys ( e.g. Pacific lamprey Entosphenus tridentatus ) and can potentially be used in the development of life‐cycle models for these species. These results also suggest that estimators derived from von Bertalanffy growth models should be interpreted with caution if there is high uncertainty in age estimates.

A clever solution to a vexing problem - Michael C. Whitlock (Molecular Ecology, 2015)
F ST (as well as related measures such as G ST ) has long been used both as a measure of the relative amount of genetic variation between populations and as an indicator of the amount of gene flow among populations. Unfortunately, F ST and its clones are also sensitive to mutation, particularly when the mutation rate per locus is greater than the migration rate among populations. Relatively high mutation rates cause estimates of F ST and G ST to be much lower than researchers sometimes expect, when migration rates are low in the studied species. Several recent suggestions for dealing with this problem have been unsatisfactory for one reason or another, and no general solution exists (if we are not to abandon these otherwise useful measures of differentiation). In an important article in this issue, Jinliang Wang (2015) shows that it is possible to identify whether the genetic markers in a given study are likely to give estimates of F ST that are strongly affected by mutation. The proposed test is simple and elegant, and with it, molecular ecologists can determine whether the F ST from their makers can be depended on for further inference about their species’ genome and the demographic forces which shaped its patterns.

The relative power of genome scans to detect local adaptation depends on sampling design and statistical method - Katie E. Lotterhos; Michael C. Whitlock (Molecular Ecology, 2015)
Although genome scans have become a popular approach towards understanding the genetic basis of local adaptation, the field still does not have a firm grasp on how sampling design and demographic history affect the performance of genome scans on complex landscapes. To explore these issues, we compared 20 different sampling designs in equilibrium (i.e. island model and isolation by distance) and nonequilibrium (i.e. range expansion from one or two refugia) demographic histories in spatially heterogeneous environments. We simulated spatially complex landscapes, which allowed us to exploit local maxima and minima in the environment in ‘pair’ and ‘transect’ sampling strategies. We compared F ST outlier and genetic–environment association ( GEA ) methods for each of two approaches that control for population structure: with a covariance matrix or with latent factors. We show that while the relative power of two methods in the same category ( F ST or GEA ) depended largely on the number of individuals sampled, overall GEA tests had higher power in the island model and F ST had higher power under isolation by distance. In the refugia models, however, these methods varied in their power to detect local adaptation at weakly selected loci. At weakly selected loci, paired sampling designs had equal or higher power than transect or random designs to detect local adaptation. Our results can inform sampling designs for studies of local adaptation and have important implications for the interpretation of genome scans based on landscape data.

Evaluation of demographic history and neutral parameterization on the performance of F ST outlier tests - Katie E. Lotterhos; Michael C. Whitlock (Molecular Ecology, 2014)
F ST outlier tests are a potentially powerful way to detect genetic loci under spatially divergent selection. Unfortunately, the extent to which these tests are robust to nonequilibrium demographic histories has been understudied. We developed a landscape genetics simulator to test the effects of isolation by distance ( IBD ) and range expansion on F ST outlier methods. We evaluated the two most commonly used methods for the identification of F ST outliers ( FDIST 2 and B aye S can, which assume samples are evolutionarily independent) and two recent methods ( FLK and B ayenv2, which estimate and account for evolutionary nonindependence). Parameterization with a set of neutral loci (‘neutral parameterization’) always improved the performance of FLK and B ayenv2, while neutral parameterization caused FDIST 2 to actually perform worse in the cases of IBD or range expansion. BayeScan was improved when the prior odds on neutrality was increased, regardless of the true odds in the data. On their best performance, however, the widely used methods had high false‐positive rates for IBD and range expansion and were outperformed by methods that accounted for evolutionary nonindependence. In addition, default settings in FDIST 2 and B aye S can resulted in many false positives suggesting balancing selection. However, all methods did very well if a large set of neutral loci is available to create empirical P ‐values. We conclude that in species that exhibit IBD or have undergone range expansion, many of the published F ST outliers based on FDIST 2 and B aye S can are probably false positives, but FLK and B ayenv2 show great promise for accurately identifying loci under spatially divergent selection.

A conceptual framework for predicting temperate ecosystem sensitivity to human impacts on fire regimes - D. B. McWethy; P. E. Higuera; C. Whitlock; T. T. Veblen; D. M. J. S. Bowman; G. J. Cary; S. G. Haberle; R. E. Keane; B. D. Maxwell; M. S. McGlone; G. L. W. Perry; J. M. Wilmshurst; et al. (Global Ecology and Biogeography, 2013)
Aim The increased incidence of large fires around much of the world in recent decades raises questions about human and non‐human drivers of fire and the likelihood of increased fire activity in the future. The purpose of this paper is to outline a conceptual framework for examining where human‐set fires and feedbacks are likely to be most pronounced in temperate forests world‐wide and to establish and test a methodology for evaluating this framework using palaeoecological records. Location T asmania, north‐western USA , southern S outh A merica and N ew Z ealand. Methods We outline a conceptual framework for predicting the sensitivity of ecosystems to human impacts on fire regimes and then use a circum‐ P acific comparison of existing historical reconstructions of fire, climate, human settlement and vegetation to evaluate this approach. Results Previous research investigating important controls on fire activity shows that the sensitivity of temperate ecosystems to human‐set fires is modulated by the frequency of natural fire occurrence, fuel moisture and fuel type and availability. Palaeoecological data from four temperate regions suggest that the effects of anthropogenic burning are greatest where fire is naturally rare, vegetation is poorly adapted to fire and fuel biomass is abundant and contiguous. Alternatively, where fire activity is naturally high and vegetation is well adapted to fire, evidence of human influence on fire and vegetation is less obvious. Main conclusions Palaeofire records suggest that the most dynamic and persistent ecosystem transitions occur where human activities increase landscape flammability through fire–vegetation feedbacks. Rapid forest transitions in biomass‐rich ecosystems such as N ew Z ealand and areas of Tasmania and southern South America illustrate how landscapes experiencing few fires can shift past tipping points to become fire‐prone landscapes with new alternative stable state communities. Comparisons of palaeoecological data from different regions with similar biophysical gradients but different human settlement histories can provide new opportunities for understanding ecosystem vulnerability to fire–climate–human interactions.

and D do not replace F ST - MICHAEL C. WHITLOCK (Molecular Ecology, 2011)
The genetic differentiation among populations is affected by mutation as well as by migration, drift and selection. For loci with high mutation rates, such as microsatellites, the amount of mutation can influence the values of indices of differentiation such as G ST and F ST . For many purposes, this effect is undesirable, and as a result, new indices such as and D have been proposed to measure population differentiation. This paper shows that these new indices are not effective measures of the causes or consequences of population structure. Both and D depend heavily on mutation rate, but both are insensitive to any population genetic process when the mutation rate is high relative to the migration rate. Furthermore, D is specific to the locus being measured, and so little can be inferred about the population demography from D . However, at equilibrium, D may provide an index of whether a particular marker is more strongly affected by mutation than by migration. I argue that F ST is a more important summary of the effects of population structure than D and that R ST or other measures that explicitly account for the mutation process are much better than G ST , , or D for highly mutable markers. Markers with lower mutation rates will often be easier to interpret.

Plant genotypic diversity does not beget root-fungal species diversity - David Johnson; Ian C. Anderson; Alison Williams; Raj Whitlock; J. Philip Grime (Plant and Soil, 2010)

The impact of epistatic selection on the genomic traces of selection - SARAH P. OTTO; MICHAEL C. WHITLOCK (Molecular Ecology, 2009)
The rapid accumulation of genomic data has led to an explosion of studies searching for signals of past selection left within DNA sequences. Yet the majority of theoretical studies investigating the traces of selection have assumed a simple form of selection, without interactions among selectively fixed sites. Fitness interactions—‘epistasis’—are commonplace, however, and take on a myriad of forms ( Whitlock et al. 1995 ; Segrè et al. 2005 ; Phillips 2008 ). It is thus important to determine how such epistasis would influence selective sweeps. On p. 5018 of this issue, Takahasi (2009) explores the effect of epistasis on genetic variation neighbouring two sites that interact in determining fitness, finding that such epistasis has a dramatic impact on the genetic variability in regions surrounding the interacting sites.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Evolutionary inference from Q ST - MICHAEL C. WHITLOCK (Molecular Ecology, 2008)
Q ST is a commonly used metric of the degree of genetic differentiation among populations displayed by quantitative traits. Typically, Q ST is compared to F ST measured on putatively neutral loci; if Q ST = F ST , this is taken as evidence of spatially heterogeneous and diversifying selection. This paper reviews the uses, assumptions and statistics of Q ST and F ST comparisons. Unfortunately, Q ST / F ST comparisons are statistically challenging. For a single trait, Q ST must be compared not to the mean F ST but to the distribution of F ST values. The sources of biases and sampling error for Q ST are reviewed, and a new method for comparing Q ST and F ST is suggested. Simulation results suggest that the distribution of neutral F ST and Q ST values are little affected by various deviations from the island model. Consequently, the distributions of Q ST and F ST are well approximated by the Lewontin–Krakauer prediction, even with realistic deviations from the island‐model assumptions.

The incomplete natural history of mitochondria - J. William O. Ballard; Michael C. Whitlock (Molecular Ecology, 2004)
Mitochondrial DNA (mtDNA) has been used to study molecular ecology and phylogeography for 25 years. Much important information has been gained in this way, but it is time to reflect on the biology of the mitochondrion itself and consider opportunities for evolutionary studies of the organelle itself and its ecology, biochemistry and physiology. This review has four sections. First, we review aspects of the natural history of mitochondria and their DNA to show that it is a unique molecule with specific characteristics that differ from nuclear DNA. We do not attempt to cover the plethora of differences between mitochondrial and nuclear DNA; rather we spotlight differences that can cause significant bias when inferring demographic properties of populations and/or the evolutionary history of species. We focus on recombination, effective population size and mutation rate. Second, we explore some of the difficulties in interpreting phylogeographical data from mtDNA data alone and suggest a broader use of multiple nuclear markers. We argue that mtDNA is not a sufficient marker for phylogeographical studies if the focus of the investigation is the species and not the organelle. We focus on the potential bias caused by introgression. Third, we show that it is not safe to assume a priori that mtDNA evolves as a strictly neutral marker because both direct and indirect selection influence mitochondria. We outline some of the statistical tests of neutrality that can, and should, be applied to mtDNA sequence data prior to making any global statements concerning the history of the organism. We conclude with a critical examination of the neglected biology of mitochondria and point out several surprising gaps in the state of our knowledge about this important organelle. Here we limelight mitochondrial ecology, sexually antagonistic selection, life‐history evolution including ageing and disease, and the evolution of mitochondrial inheritance.

Simulating Historical Variability in the Amount of Old Forests in the Oregon Coast Range - Michael C. Wimberly; Thomas A. Spies; Colin J. Long; Cathy Whitlock (Conservation Biology, 2000)
We developed the landscape age‐class demographics simulator ( LADS) to model historical variability in the amount of old‐growth and late‐successional forest in the Oregon Coast Range over the past 3,000 years. The model simulated temporal and spatial patterns of forest fires along with the resulting fluctuations in the distribution of forest age classes across the landscape. Parameters describing historical fire regimes were derived from data from a number of existing dendroecological and paleoecological studies. Our results indicated that the historical age‐class distribution was highly variable and that variability increased with decreasing landscape size. Simulated old‐growth percentages were generally between 25% and 75% at the province scale (2,250,000 ha) and never fell below 5%. In comparison, old‐growth percentages varied from 0 to 100% at the late‐successional reserve scale (40,000 ha). Province‐scale estimates of current old‐growth (5%) and late‐successional forest (11%) in the Oregon Coast Range were lower than expected under the simulated historical fire regime, even when potential errors in our parameter estimates were considered. These uncertainties do, however, limit our ability to precisely define ranges of historical variability. Our results suggest that in areas where historical disturbance regimes were characterized by large, infrequent fires, management of forest age classes based on a range of historical variability may be feasible only at relatively large spatial scales. Comprehensive landscape management strategies will need to consider other factors besides the percentage of old forests on the landscape, including the spatial pattern of stands and the rates and pathways of landscape change.